Social perceptions versus meteorological observations of snow and winter along the Front Range - Milligan, William James, author; Fassnacht, Steven, advisor; DiEnno, Cara, committee member; De Miranda, Michael, committee member (Colorado State University. Libraries, 2013)
This research aims to increase understanding of Front Range residents' perceptions of snow, winter and hydrologic events. This study also investigates how an individual's characteristics may shape perceptions of winter weather and climate. A survey was administered to determine if perceptions of previous winters align with observed meteorological data. The survey also investigated how individual characteristics influence perceptions of snow and winter weather. The survey was conducted primarily along the Front Range area of the state of Colorado in the United States of America. This is a highly populated semi-arid region that acts as an interface between the agricultural plains to the east that extend to the Mississippi River and the Rocky Mountains to the west. The climate is continental, and while many people recreate in the snowy areas of the mountains, most live where annual snowfall amounts are low. Precipitation, temperature, and wind speed datasets from selected weather stations were analyzed to determine correct survey responses. Survey analysis revealed that perceptions of previous winters do not necessarily align with observed meteorological data. The mean percentage of correct responses to all survey questions was 36.8%. Further analysis revealed that some individual characteristics (e.g. winter recreation, source of winter weather information) did influence correct responses to survey questions.
Keywords: perception; snow